Análisis del TLC celebrado entre Estados Unidos y Colombia en el sector agrícola: ¿Se está cumpliendo con las expectativas? (2014)
ABSTRACT Currently the eyes of the government are focus on macroeconomic analysis and the impact of the trade promotion agreement concluded between Colombia and the United States considering that the opening of trade borders increase in the medium -term economic , social and technological growth in key sectors productive in the country. However, they have not considered the consequences that are currently showing in an industry that represents a significant share in the PIB: the agricultural sector.